Comparative efficacy of Chinese herbal injections for angina pectoris: A Bayesian network meta-analysis of randomized controlled trials. (April 2019) - Wang, Kaihuan; Wu, Jiarui; Duan, Xiaojiao; Zhang, Dan; Lin, Xi; Zhang, Sixuan; Ni, Mengwei; Liu, Shuyu; Meng, Ziqi; Gao, Xiaoyan; Tan, Peng; Liu, Yonggang
Highlights: This Bayesian network meta-analysis focused on the comparative efficacy of Chinese herbal injections in the treatment of angina pectoris for the first time, aiming to provide more sight for selection of angina pectoris treatment and strengthened by a comprehensive literature search, strict eligible criteria, and rigorous analysis. Integrating network meta-analysis results, Shenqi Fuzheng injection plus western medicine therapy and Shenmai injection plus western medicine therapy were more officious in the treatment of angina pectoris. Huangqi injection plus western medicine therapy and Shenmai injection plus western medicine therapy performed pretty well in improving hemorheology index and serum lipid parameter for angina pectoris patients. Abstract: Objective: The severity of angina pectoris has been recognized. It is believed that Chinese herbal injections have an outstanding clinical effect on this condition. This network meta-analysis was devised to investigate the comparative efficacy of eight Chinese herbal injections (Ciwujia injection, Dazhuhongjingtan injection, Huangqi injection, Shenfu injection, Shengmai injection, Shenmai injection, Shenqi Fuzheng injection, Yiqifumai injection) in the treatment of angina pectoris. Methods: A literature search was performed in PubMed, Embase, and the Cochrane Library, Chinese Biological Medicine Database, China National Knowledge Infrastructure, Wanfang Database, and Chinese Scientific Journal Database from their inception to June 25, 2018. A pre-designed eligibility criterion was utilized in this network meta-analysis, and a methodological quality analysis was conducted. Data analysis was performed by WinGUGS 1.4.3, Stata 13.0 and TSA software, and the odds ratio or mean difference with the 95% credible interval was reported for symptomatic improvement, electrocardiography improvement, fibrinogen, triglyceride and cholesterol. The ranking probability of interventions in various outcomes was also utilized. Results: A total of 73 randomized controlled trials with 6639 patients were identified. Integrating network meta-analysis results, Shenqi Fuzheng injection plus western medicine therapy and Shenmai injection plus western medicine therapy were shown to be more efficacious than other therapies. In addition, Huangqi injection plus western medicine therapy and Shenmai injection plus western medicine therapy performed well in improving the haemorheology index and serum lipid parameters. Conclusions: Eligible Chinese herbal injections plus western medicine therapy might have a better impact on angina pectoris patients than western medicine therapy alone. While this study had limitations, the findings should be interpreted with caution. In addition, more high-quality randomized controlled trials with a large sample must be conducted to support this study.